The Role of Reflective Practice in Teacher Education: A Comprehensive Review - Aarti Sharma, Nazia Jamal, Monica Verma, Nikita Jain, E. Muthukumar, (European Economic Letters (EEL), 2024)
Reflective practice has emerged as a pivotal component in teacher education, fostering ongoing professional development and enhancing teaching efficacy. This review paper examines the multifaceted role of reflective practice in teacher education through a comprehensive analysis of existing literature. By synthesizing empirical studies, theoretical frameworks, and practical applications, this review provides a nuanced understanding of how reflective practice influences teacher learning, instructional strategies, and student outcomes. The review begins by elucidating the theoretical underpinnings of reflective practice, drawing on seminal works by scholars such as Dewey, Schön, and Kolb. It explores the evolution of reflective practice from a theoretical concept to a pedagogical approach that is widely adopted in teacher education programs worldwide. Through an examination of various models and frameworks, including Gibbs’ Reflective Cycle and Brookfield’s Critical Reflection, the paper delineates the diverse ways in which reflective practice can be implemented and integrated into teacher preparation courses. Furthermore, this review highlights the empirical evidence supporting the efficacy of reflective practice in enhancing teacher professionalism and effectiveness. It discusses how reflective activities, such as journaling, peer observation, and action research, promote self-awareness, critical thinking, and pedagogical innovation among pre-service and in-service teachers. Additionally, the paper explores the role of reflective supervision and mentoring in facilitating reflective practice and fostering a culture of continuous improvement within educational institutions. Moreover, the review addresses the challenges and limitations associated with implementing reflective practice in teacher education, including issues of time constraints, resistance to change, and the need for ongoing support and scaffolding. Finally, it offers recommendations for future research directions and practical implications for enhancing the integration of reflective practice into teacher education programs, ultimately striving towards the cultivation of reflective practitioners who are equipped to meet the diverse needs of 21st-century learners.